DETERMINATION OF RUTIN IN LEAVES OF SALIX TRIANDRA USING THE METHOD OF PLANAR CHROMATOGRAPHY - E. G. Sannikova; T. D. Mezenova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2016)
The aim of the study is to develop new methods of identification and quantitative determination of rutin in the leaves of Salix triandra L. with thin-layer chromatography. The digital processing of the chromatograms was performed using «Sorbfil Videodensitometer» computer program (Krasnodar). For the chromatography analysis we used plates «Sorbfil» PTSH-P-A-UV, mobile phase: n-butanol-glacial acetic acid-water (4:1:1), detecting reagent - ammonia vapors. The rutin is detected as yellow spots with Rf 0.64±0.02. The detection limit is 0.5 μg/μl. The regression equation has the form: S=4.75×103 m. With the use of this method we found that the composition of rutin in leaves of Salix triandra was in the range 1.81±0.06% on the air-dry raw material (relative standard deviation RSD%=2.5%; the measurement error E=3.12%). The method is sensitive, linear, has a small error, and does not require expensive equipment.